2015
DOI: 10.1177/1357633x15600583
|View full text |Cite
|
Sign up to set email alerts
|

Impact on clinical events and healthcare costs of adding telemedicine to multidisciplinary disease management programmes for heart failure: Results of a randomized controlled trial

Abstract: Among patients managed in the setting of a comprehensive HF programme, the addition of telemedicine may result in better outcomes and reduction of costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
146
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(159 citation statements)
references
References 23 publications
4
146
0
6
Order By: Relevance
“…There is emphasis on the high level of satisfaction shown by patients who are part of the project, as they feel better controlled and safer. This data confirms the feasibility of a telemedicine project in chronic elderly patients, despite their limited experience in the use of electronic devices [39][40][41][42].…”
Section: Conclusion and Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…There is emphasis on the high level of satisfaction shown by patients who are part of the project, as they feel better controlled and safer. This data confirms the feasibility of a telemedicine project in chronic elderly patients, despite their limited experience in the use of electronic devices [39][40][41][42].…”
Section: Conclusion and Discussionsupporting
confidence: 64%
“…Also hospital readmission for any cause and the average number of days in the hospital was significantly reduced. In addition, the study we have shown that the efficiency of telemedicine was independent of education level, the severity of HF, the presence of depressive symptoms or the fragility of the patient [40][41][42].…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…17,18 In this type of unit or program, a variety of interventions may be carried out (education, follow-up, treatment, social support) from those that have been demonstrated to improve quality of life, reduce the number of hospital admissions for HF and for all causes, and even reduce mortality. 5,6 This reduction in hospital admissions 4,14,15,[19][20][21] and improved survival have also been demonstrated in Spain.…”
Section: Introductionmentioning
confidence: 72%
“…Most HFUs combine several of these interventions. [4][5][6][7][13][14][15][16] The increasing use of these care systems has been perceived favorably due to the initial results from many studies and meta-analyses, 5,6 leading to their level IA recommendation in clinical practice guidelines. 17,18 In this type of unit or program, a variety of interventions may be carried out (education, follow-up, treatment, social support) from those that have been demonstrated to improve quality of life, reduce the number of hospital admissions for HF and for all causes, and even reduce mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation